2014
DOI: 10.3233/thc-140850
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of bone scintigraphy for aseptic loosening after total knee arthroplasty

Abstract: BACKGROUND: Despite technical improvements, aseptic loosening after total knee arthroplasty (TKA) remains a frequent complication. A one-stage revision arthroplasty is the most common therapeutic pathway. OBJECTIVE: The aim of this study was to evaluate the diagnostic value of bone scintigraphy in detecting aseptic loosening after TKA. METHODS: We retrospectively identified 46 cases of one-stage revision TKA performed between January 2011 and December 2012. In each case a bone scintigraphy was performed at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…A meta-analysis by Temmerman et al reported a pooled sensitivity and speci city for plain radiography of 82% and 81%, respectively 15 . The most recent study on bone scintigraphy by Claassen et al reported a sensitivity of 76% and a speci city of 83% 16 . Interestingly, planar nuclear arthrography on its own has a low reported sensitivity and speci city of 87% and 64% [15].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Temmerman et al reported a pooled sensitivity and speci city for plain radiography of 82% and 81%, respectively 15 . The most recent study on bone scintigraphy by Claassen et al reported a sensitivity of 76% and a speci city of 83% 16 . Interestingly, planar nuclear arthrography on its own has a low reported sensitivity and speci city of 87% and 64% [15].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Temmerman et al reported a pooled sensitivity and speci city for plain radiography of 82% and 81%, respectively 15 . The most recent study on bone scintigraphy by Claassen et al reported a sensitivity of 76% and a speci city of 83% 16 . Interestingly, planar nuclear arthrography on its own has a low reported sensitivity and speci city of 87% and 64% [15].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Temmerman et al reported a pooled sensitivity and specificity for plain radiography of 82% and 81%, respectively (Temmerman et al 2005). The most recent study on bone scintigraphy by Claassen et al reported a sensitivity of 76% and a specificity of 83% (Claassen et al 2014). Interestingly, planar nuclear arthrography on its own has a low reported sensitivity and specificity of 87% and 64% (Temmerman et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study on bone scintigraphy by Claassen et al . reported a sensitivity of 76% and a specificity of 83% (Claassen et al 2014 ). Interestingly, planar nuclear arthrography on its own has a low reported sensitivity and specificity of 87% and 64% (Temmerman et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%